2017
DOI: 10.1111/1556-4029.13691
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Alcohol‐Based Hand Sanitizer Vapors on Evidential Breath Alcohol Test Results

Abstract: This study was undertaken to determine if the application of alcohol-based hand sanitizers (ABHSs) to the hands of a breath test operator will affect the results obtained on evidential breath alcohol instruments (EBTs). This study obtained breath samples on three different EBTs immediately after application of either gel or foam ABHS to the operator's hands. A small, but significant, number of initial analyses (13 of 130, 10%) resulted in positive breath alcohol concentrations, while 41 samples (31.5%) resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…On a limited-scale study, Brewer and Streel showed that disulfiram-ethanol reaction might be caused by inhaling alcohol from ABHSs in confined spaces [9] . Strawsine and Lutmer showed that ABHSs could drive increased breath alcohol levels in around 10% of the subjects, causing mouth alcohol effects, and recommended caution in using these products 15 minutes before testing [8] . As seen from these studies, none tried to replicate the use of ABHS in cars by drivers tested with a breathalyzer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On a limited-scale study, Brewer and Streel showed that disulfiram-ethanol reaction might be caused by inhaling alcohol from ABHSs in confined spaces [9] . Strawsine and Lutmer showed that ABHSs could drive increased breath alcohol levels in around 10% of the subjects, causing mouth alcohol effects, and recommended caution in using these products 15 minutes before testing [8] . As seen from these studies, none tried to replicate the use of ABHS in cars by drivers tested with a breathalyzer.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study reported by the Texas Poison Control Centers has shown an overall 72.5% increase in reported exposures to ABHS between 2019 and 2020 [5] . In addition, some studies revealed a potential effect of alcohol vapors from hand sanitizers on the breath alcohol tests [6] , [7] , suggesting they might lead to false positives, at least for 15 minutes after their use [8] . Almost all alcohol from ABHS is inhaled, the skin absorption being unable to yield positive BAC or BrAC results with clinical significance [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Two studies have measured BrAC in humans during, but not after, exposure to ethanol [19,20]. Several investigators have studied BrAC after use of ethanol containing hand sanitizers [8,9,21], see also review by McClean et al [10]. Although exposure via hand sanitizers is realistic from a practical point of view, the BrAC data are difficult to interpret as the inhaled concentration of ethanol were unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For example, people sometimes use mouthwash as an explanation for a positive breath test [5]. Other examples of potential confounders are E-cigarette smoking (as the E-liquid may contain ethanol) [6,7], use of alcohol-based hand rubs, disinfectants or cleaners [8][9][10] and, oddly, alcohol spill in the car [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation